Loess Strata Distribution Characteristics and Paleoclimate Spatial Pattern during the Last Interglacial in the Luohe River Basin - Jiao Guo; Jiansheng Shi; Hongyun Chen; Chao Song; Qiuyao Dong; Wei Wang (Geosciences, 2023)
Paleoclimate studies of loess in China have focused mostly on the time series of a single borehole or profile. However, research on loess strata and regional paleoenvironmental patterns could facilitate a deeper understanding of loess as a paleoenvironmental indicator and provide new insights into interpreting loess in sedimentary records of the paleoclimate. In this study, we determined the spatial pattern and regional characteristics of the paleoclimate during the Last Interglacial period in the Luohe River Basin, Shaanxi Province, China. We selected four representative boreholes in the study area (ZK04, ZK18, ZK13, and ZK19) from different landforms and zones, distributed from the northwest to the southeast, as well as three classic profiles (JB, JD, and LC). From north to south, comparative analyses were conducted of the loess strata, magnetic susceptibility, and grain size, and we analyzed the distribution characteristics of loess and paleosols in different geomorphological regions. The results showed that both the thickness and the sedimentation rate of loess in this river basin decreased from north to south. There were few paleosol horizons in the northern Liangmao area, but numerous such horizons in the southern plateau, and the degree of paleosol development increased from north to south. The magnetic susceptibility increased, whereas the particle composition tended to become thinner from north to south. The climate fluctuations of the Last Glacial recorded by the loess and paleosols in different regions were inconsistent.